Please help me with my question!!
Please help me with my question!! - 1

Answers

Answer 1
Answer:

Answer:

Step-by-step explanation:

y = 10x + 50

x ---> no of weeks

y - intercept = 50

Answer 2
Answer: Y= 450 only becuase if not it will work

Related Questions

A student was asked to use the formula for the perimeter of a rectangle, P = 2l + 2w, to solve for l. The student came up with an answer, P -2w=2l. What error did The student make? Explain. Then solve for l
What is the equation of the line perpendicular to 2x − 5y = −35 that contains the point (10, 4)?
Evaluate b+c when a=5, b= 17, and c= 25
Find 1+2+3+4+ ... +40, the sum of the first 40 natural numbers.The sum is
X2−4=0 Which is the solution set for the equation above?

The cost of 6 sailor moon comic books is equal to the cost of a Nirvana vinyl plus 3 comic books. The vinyl costs $15. How much is one comic book?

Answers

Answer:

one comic book costs $5

Step-by-step explanation:

let cost of comic book = $x

let cost of vinyl  = $y

according to the question:

6x = y + 3x

y = 6x - 3x

y = 3x                 (1)

y = $15               (2)

substituting the value of y from equation (2) into equation (1)

15 = 3x

x = 15/3 = 5

thus, cost of one comic book = $5

Answer:

5$.

Step-by-step explanation:

Let's denote the cost of one Sailor Moon comic book as x .

The cost of 6 Sailor Moon comic books is 6x.

According to the given information, the cost of a Nirvana vinyl plus 3 comic books is equal to the cost of 6 Sailor Moon comic books.

So, 15 + 3x = 6x , as the vinyl costs $15.

Now, let's solve for x :

Subtract 3x from both sides: 15 = 3x

Divide by 3: x = 5

Therefore, the cost of one Sailor Moon comic book is $5.

When evaluating algebraic expressions, the first thing is to

Answers

Answer:

When evaluating an algebraic expression the first thing you do is that you observe what would be the first operation applied on the expression.

In order to determine that you need to know the basic concept of PEMDAS

Where as  

P stands for Parentheses (brackets)

E stands for exponents

M stands for multiplication

D stands for division

A stands for addition  

S stands for subtraction

This is the order that needs to be kept in mind while solving the expression

You have to use the order of operations when evaluating algebraic expressions. The mnemonic device is PEMDAS, which stands for Parentheses, Exponents, Multiplication, Division, Addition, Subtraction. So the first thing is to solve what's in the parentheses.

Divide. (6a4 + 2a3) ÷ 2a

Answers

(6a^4+2a^3):2a=(6a^4+2a^3)/(2a)=(6a^4)/(2a)+(2a^3)/(2a)=3a^3+a^2\n\n\nD:a\neq0

The steps below show the incomplete solution to find the value of x for the equation 5x – 3x – 5 = –3 + 23:Step 1: 5x – 3x – 5 = –3 + 23
Step 2: 5x – 3x – 5 = 20
Step 3: 2x – 5 = 20

Which of these is most likely the next step?

Answers

Maybe step 3 because you try to get rid of the x on both sides

Anthony bought a rug for his office. He made a scale drawing of the office using a scale of 1 in = 4 ft.What is the area of the office floor not covered by the rug?

Answers

464 ft
28 times 28 = 784
20 times 16 = 320
784-320 =464 ft
So the first one

If a function f ( x ) has values f ( 4 ) = 6 and f ( 8 ) = 18, use what you have learned about function patterns to find f ( 16 ) = if f ( x ) is: a.) Linear function: f ( 16 ) = b.) Power function: f ( 16 ) = c.) Exponential function: f ( 16 ) = d.) Logarithmic function: f ( 16 ) =

Answers

Answer:

a) f(16) = 42

b) f(16) = 54

c) f(16) = 162

d) f(16) = 30

Step-by-step explanation:

a) y = mx + b ∧ m = (f(8) - f(4))/(8-4) ⇒ m = (18 - 6)/(8 - 4) = 3

b = y - mx = 6 - 3(4) = 6 - 12 = - 6

f(16) = 3(16) - 6 = 42

b) y = kxⁿ ∧ f(4) = 6 = k4ⁿ ∧ f(8) = 18 = k8ⁿ ⇒ 18/6 = (k8ⁿ)/(k4ⁿ) ⇒ 3 = 2ⁿ

n = ㏑(3) / ㏑(2) ⇒ k = y/xⁿ ⇒ k = 6/4ⁿ = 2/3

f(16) = 2/3 × 16ⁿ = 54

c) y = aeᵇˣ ∧ f(4) = 6 = aeᵇ⁴ ∧ f(8) = 18 = aeᵇ⁸ ⇒ 18/6 = (aeᵇ⁸)/(aeᵇ⁴) ⇒ 3 = e⁴ᵇ

b = ㏑(3/4) ∧ a = y / eᵇˣ ⇒ a = 6 / e⁴ᵇ = 2

f(16) = 2eᵇ¹⁶ = 162

d) y = a㏑(bx) ∧ f(4) = 6 = a㏑(b4) ∧ f(8) = 18 = a㏑(b8)

⇒ 18 - 6 = a㏑(b8) - a㏑(b4) ⇒ 12 = a㏑(8b/4b) ⇒ a = 12 / ㏑(2)

f(4) = 6 = a㏑(4b) ⇒ b = (√2)/4

f(16) = a㏑(b16) = 30